2020
DOI: 10.1103/physrevb.101.094504
|View full text |Cite
|
Sign up to set email alerts
|

Topological superconducting phases and Josephson effect in curved superconductors with time reversal invariance

Abstract: We consider a Rashba spin-orbit coupled nanowire with anisotropic spin-singlet superconducting pairing and time-reversal-invariant symmetry. We explore the evolution of the topological superconducting phases of this system due to geometric deformations for the representative case of a wire bent in a semielliptical shape. We find that when the system is in its topological superconducting phase, strong inhomogeneities in the profile curvature can produce a pair of localized eigenmodes, which can be attributed to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…[31] Recent proposals have predicted the possibility to realize topological superconductivity by hybridizing ordinary superconductors with helical materials, with the help of magnetic perturbations. The curved geometric profile also allows for tuning the spin correlations of the superconducting state via the induced inhomogeneity of the spin-orbit coupling that affects the Josephson critical current [707] and, in curved nanostructures with Rashba spinorbit coupling, leads to nontrivial textures of spin-triplet pairs. [11] Due to the geometric Meissner effect, 2D chiral superconductors on curved surfaces have been shown to spontaneously develop a magnetic flux.…”
Section: State Of the Artmentioning
confidence: 99%
“…[31] Recent proposals have predicted the possibility to realize topological superconductivity by hybridizing ordinary superconductors with helical materials, with the help of magnetic perturbations. The curved geometric profile also allows for tuning the spin correlations of the superconducting state via the induced inhomogeneity of the spin-orbit coupling that affects the Josephson critical current [707] and, in curved nanostructures with Rashba spinorbit coupling, leads to nontrivial textures of spin-triplet pairs. [11] Due to the geometric Meissner effect, 2D chiral superconductors on curved surfaces have been shown to spontaneously develop a magnetic flux.…”
Section: State Of the Artmentioning
confidence: 99%
“…In these systems curvature has two main consequences: the appearance of a quantum geometric potential causing interesting phenomena at the nanoscale [24][25][26][27] and of a strain field producing a curvature-induced Rashba-type spin-orbit coupling (SOC) [28][29][30]. Theoretical studies have focused on new properties appearing in semiconductors [31][32][33][34] as well as in superconductors [35][36][37]. For instance, it was shown that geometric curvature can promote topological edge states in bent quantum wire with Rahsba SOC [32] and topological superconductivity in curved 2D topological insulators [37].…”
Section: Introductionmentioning
confidence: 99%
“…While the emergence of π states is typically bound to occur in superconductor/ferromagnet/superconductor junctions [14][15][16] , due to the extra π shift originating from the exchange coupling in the ferromagnetic layer, the role of spin-orbit fields can bring additional channels for the generation and control of 0-π transitions. Indeed, a π-Josephson effect and 0-π transitions can be realized in NCS-NCS junctions with the two NCSs having opposite orientation of the Rashba spin-orbit field 17 or by interfacing nanowires with low-dimensional electronic channels having non-trivial geometric shape at the nanoscale 18 . An anomalous Josephson current phase relation (CPR) can be also obtained by engineering magnetic quantum-dots at the NCS/s-wave spin-singlet superconductor (SSC) interface 19 .…”
Section: Introductionmentioning
confidence: 99%